2009
DOI: 10.1083/jcb.200902128
|View full text |Cite
|
Sign up to set email alerts
|

Bub1 regulates chromosome segregation in a kinetochore-independent manner

Abstract: The kinetochore-bound protein kinase Bub1 performs two crucial functions during mitosis: it is essential for spindle checkpoint signaling and for correct chromosome alignment. Interestingly, Bub1 mutations are found in cancer tissues and cancer cell lines. Using an isogenic RNA interference complementation system in transformed HeLa cells and untransformed RPE1 cells, we investigate the effect of structural Bub1 mutants on chromosome segregation. We demonstrate that Bub1 regulates mitosis through the same mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
283
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 193 publications
(306 citation statements)
references
References 53 publications
17
283
6
Order By: Relevance
“…Mad1-Mad2 first catalyzes MCC assembly at interphase nuclear pores [3], then migrates to kinetochores at nuclear envelope breakdown (NEBD) and resumes MCC assembly until bipolar spindle attachment is complete [1,2]. There is significant debate about the factor(s) involved in targeting Mad1-Mad2 to kinetochores in higher eukaryotes [4][5][6][7][8][9]. Through gene editing and livecell imaging, we found that the human Rod-Zw10-Zwilch (RZZ) complex is dispensable for cell viability and initial recruitment of Mad1-Mad2 to kinetochores at NEBD, but then becomes necessary to tether Mad1-Mad2 at kinetochores and sustain SAC arrest in cells challenged with spindle poisons.…”
Section: Discussionmentioning
confidence: 99%
“…Mad1-Mad2 first catalyzes MCC assembly at interphase nuclear pores [3], then migrates to kinetochores at nuclear envelope breakdown (NEBD) and resumes MCC assembly until bipolar spindle attachment is complete [1,2]. There is significant debate about the factor(s) involved in targeting Mad1-Mad2 to kinetochores in higher eukaryotes [4][5][6][7][8][9]. Through gene editing and livecell imaging, we found that the human Rod-Zw10-Zwilch (RZZ) complex is dispensable for cell viability and initial recruitment of Mad1-Mad2 to kinetochores at NEBD, but then becomes necessary to tether Mad1-Mad2 at kinetochores and sustain SAC arrest in cells challenged with spindle poisons.…”
Section: Discussionmentioning
confidence: 99%
“…Recent experiments both in fission yeast and human cells suggest that such a behavior is not only limited to the effector proteins, but can also be found for the more upstream kinase Bub1 (Klebig et al 2009;Windecker et al 2009). A first study based on a structure-function study of human Bub1 mutants in an Bub1 RNAi background, indicates that Bub1 does not need to be located at the kinetochores to control chromosome congression and spindle assembly checkpoint even though there is a minor impairment of each function (Klebig et al 2009).…”
Section: Checkpoint Function At Kinetochores Versus Cytoplasmmentioning
confidence: 99%
“…Indeed, all three spindle checkpoint kinases, Mps1, BubR1, and Bub1, regulate and sometimes correct defective kinetochore-microtubule attachments (Kops 2009;Kops et al 2010;Musacchio and Salmon 2007). Importantly, Bub1 and BubR1 separation of function mutants have demonstrated that this ability to regulate kinetochoremicrotubule attachments is independent of their capacity to control spindle checkpoint signaling (Elowe et al 2010;Klebig et al 2009;Malureanu et al 2009;Warren et al 2002). BubR1 controls the dynamics of kinetochore-bound microtubules, while Bub1 has been proposed to contribute to the transition of lateral kinetochore-microtubule attachments to end-on attachments during chromosome alignment (Gillett et al 2004;Lampson and Kapoor 2005;Meraldi and Sorger 2005).…”
Section: Is It Only Checking Kinetochore-microtubulementioning
confidence: 99%
See 2 more Smart Citations